Ciliate species from tank-less bromeliads in a dry tropical forest and their geographical distribution in the Neotropics - Durán-Ramírez, Carlos Alberto; Mayén-Estrada, Rosaura (Zootaxa, 2018)
The study of ciliate diversity in tropical environments remains scarce. In Neotropical forests, bromeliads are a common component of the vascular flora; bromeliads with tank morphology intercept rain water and detritus, resulting in the formation of a phytotelm, where heterotrophic protist communities like ciliates can establish. However, it is not known if ciliates inhabit tank-less bromeliads. For this reason, the goal of the present study was to investigate if ciliates can establish between the leaf axils of five terrestrial and epiphytic tank-less bromeliad species in a dry tropical forest in west Mexico. We collected samples of rain water and detritus from the leaf axils during the humid season of years 2015 and 2016. For ciliate taxonomical identification, we used optical microscopy, in vivo observation, and silver impregnation techniques. To summarize information about geographical distribution of ciliates identified at species level in the Neotropics, we provided their records from previous works, at country level with locality and georeferenciation. We recorded 27 taxa of ciliates, where the class Oligohymenophorea contained the largest richness of taxa. Drepanomonas revoluta, Leptopharynx bromeliophilus, and Tetrahymena sp. were recorded from all the species of bromeliads. Bromelia karatas was the species that hosted the largest number of ciliate taxa (22). Our results indicated that Glaucomides bromelicola, Gonostomum bromelicola, Leptopharynx bromelicola and L. bromeliophilus, species which are considered endemic to tank bromeliads, can also inhabit tank-less bromeliads. We provided previous records of 19 ciliate species from eleven countries within the Neotropical region, and Bromeliothrix metopoides was the species most frequently recorded in Neotropical countries (9). Therefore, tank-less bromeliads can constitute a temporal habitat for ciliates, and function as cysts reservoirs in environments with a pronounced seasonality like dry tropical forests.